2016
DOI: 10.1128/genomea.00446-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Pseudomonas fluorescens LBUM636, a Strain with Biocontrol Capabilities against Late Blight of Potato

Abstract: Herein provided is the full-genome sequence of Pseudomonas fluorescens LBUM636. This strain is a plant growth-promoting rhizobacterium (PGPR) which produces phenazine-1-carboxylic acid, an antibiotic involved in the biocontrol of numerous plant pathogens, including late blight of potato caused by the plant pathogen Phytophthora infestans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Very few culturable strains of P. yamanorum are known (8H1 (Arnau et al, 2015), LP2 (Komesli et al, 2020), LBUM636 (Morrison et al, 2016)), and P. arsenicoxi dans (VC-1 (Campos et al, 2010)), however, only P. arsenicoxydans ACM1 (GenBank: ASM413599v1) was isolated from the moss rhizosphere in Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…Very few culturable strains of P. yamanorum are known (8H1 (Arnau et al, 2015), LP2 (Komesli et al, 2020), LBUM636 (Morrison et al, 2016)), and P. arsenicoxi dans (VC-1 (Campos et al, 2010)), however, only P. arsenicoxydans ACM1 (GenBank: ASM413599v1) was isolated from the moss rhizosphere in Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…The phenazines are small molecules that can penetrate different types of cells, including prokaryotes. Many phenazines present antimicrobial activity, suppressing pathogenic microorganisms of humans, animals and plants, also playing an important role in the survival strategies of bacteria in the environment (Chen et al, 2014 ; Briard et al, 2015 ; Dasgupta et al, 2015 ; Garrison et al, 2016 ; Morrison et al, 2016 ). The P. aeruginosa LV strain is a great producer of phenazine carboxylic acid (PCA).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the complete genome of Pseudomonas fluorescens LBUM636, a strain with significant biocontrol activity against Phytophthora infestans , was sequenced, providing a bioinformatic reference for mining biocontrol mechanisms 54 . Subsequently, it was reported that phenazine‐1‐carboxylic acid (PCA), produced by Pseudomonas fluorescens strain LBUM636, probably plays a key role in the biocontrol activity of this strain against Phytophthora infestans , which was revealed through comparisons between the wild‐type strain and its isogenic mutant phzC‐ that does not produce PCA 55 .…”
Section: Bacteria As Biocontrol Agents and Their Modes Of Actionmentioning
confidence: 99%